TINGKAT PREVALENSI STOMATITIS PADA KUCING - Nugroho, Tri Ananda Erwin; Gubali, Syukri I (Gorontalo Journal of Equatorial Animals, 2025)
ABSTRACTThe aim of this research is to measure the incidence rate (prevalence) of stomatitis cases in cats treated at the Gorontalo City Animal Health Center (Puskeswan). Stomatitis is inflammation of the oral cavity, gums and tongue accompanied by ulcers and necrosis. The samples examined were cats that had stomatitis and sought treatment at the Gorontalo City Health Center from January to March 2024. The examination method was to examine the patient's ambulator. The patient's ambulator is the first record when the patient is handled. Cat patients who come have an anemsa by asking the animal owner several questions, which are then recorded in the ambulator. After the patient's analysis is carried out, a physical examination is carried out by measuring body temperature, listening to the respiratory tract using a microscope, which aims to find out whether only the digestive system is affected or whether the respiratory system has been attacked. The mouth is then opened to determine the condition of the inside of the mouth. The parts observed include the upper lower lip, upper and lower tongue, right and left gums, the roof of the mouth and the patient's teeth. The prevalence of stomatitis in cats treated at the Gorontalo City Health Center was calculated by dividing the number of patients treated during January to March 2024 by one hundred percent. The data was then analyzed descriptively. The prevalence of Stomatitis in cats receiving treatment from January to March at the Gorontalo City Health Center was 25.7%.